A promising biomarker of elevated galanin level in hypothalamus for osteoporosis risk in type 2 diabetes mellitus. (March 2021) - Fang, Penghua; She, Yuqing; Han, Long; Wan, Shiwei; Shang, Wenbin; Zhang, Zhenwen; Min, Wen
Highlights: Galanin is involved in the pathogenesis of T2DM and osteoporosis. Galanin increases insulin sensitivity as well as bone density and mass in animal models. GALR2 agonist may be taken as a novel therapeutic strategy to treat both diseases. Abstract: Type 2 diabetes mellitus (T2DM) and osteoporosis are two major healthcare problems worldwide. T2DM is considered to be a risk factor for osteoporosis. Interestingly, several epidemiological studies suggest that bone abnormalities associated with diabetes may differ, at least in part, from those associated with senile or post-menopausal osteoporosis. The growing prevalence that patients with T2DM simultaneously suffer from osteoporosis, puts forward the importance to discuss the relationship between both diseases, as well as to investigate correlative agents to treat them. Emerging evidences demonstrate that neuropeptide galanin is involved in the pathogenesis of T2DM and osteoporosis. Galanin via activation of central GALR2 increases insulin sensitivity as well as bone density and mass in animal models. The disorder of galanin function plays major role in development of both diseases. Importantly, galanin signaling is indispensable for ΔFosB, an AP1 antagonist, to play the bone mass-accruing effects in the ventral hypothalamic neurons of diabetic models. This review summarizes our and other recent studies to provide a new insight into the multivariate relationship among galanin, T2DM and osteoporosis, highlighting the beneficial effect of galanin on the comorbid state of both diseases. These may help us better understanding the pathogenesis of osteoporosis and T2DM and provide useful clues for further inquiry if elevated galanin level may be taken as a biomarker for both conjoint diseases, and GALR2 agonist may be taken as a novel therapeutic strategy to treat both diseases concurrently.